Heritage child stars on Disney+: the liquidities of child stardom in the SVOD era. Issue 2 (3rd April 2023) - Baker, Djoymi; Balanzategui, Jessica
ABSTRACT: Disney is a brand long associated with the production of family content and a continually replenished suite of child stars. The 2019 launch of Disney+ leveraged these heritage child stars in its tightly curated home page, stressing nostalgia and a wholesome brand image around the figure of the child. This article explores how the Disney+ interface aesthetics, catalogue organisation and other paratexts negotiate heritage child stars in the context of managing the Disney brand narrative in the streaming era. Streaming interfaces offer a new form of star ephemera, as former child stars are recontextualised under new thematic banners on Disney+. However, this careful curation on the Disney+ interface is ultimately unable to contain the instability of child stars as emblems of lost youth, a tension that becomes particularly evident in the case of Lindsay Lohan and Macaulay Culkin.